Sining Dance and Central Aceh Tourism - Yanti, Meipur; Cahyono, Agus; Syakir, Syakir (Universitas Negeri Semarang, 2018)
Sining dance is the parent of dances in Gayo. Sining dance is one of traditional dances that supports the development of tourism in Central Aceh. The purpose of this research is to analyze the Sining dance and its role of tourism in Central Aceh. The research method was qualitative descriptive and used ethnographic approach.The data collection was used techniques of observation, deep interview, and document study. Data validation was done with data triangulation, source triangulation, and method triangulation while the the analysis used data reduction, data presentation, and verification/conclusion drawing. The results show that the performance of Sining dance plyas a role as cultural attraction, Sining dance also becomes one of tourism attraction through documenter video, Sining dance in one of presentation in a show, and Sining dance is a means of entertainment. The occurence of Sining dance in tourism influences the economic benefit of Central Aceh community and automatically it can preserved Sining dance itself. This research is useful as a vehicle for developing studies on traditional art problems, and is useful as an empirical input for relevant government agencies.